2022
DOI: 10.1155/2022/3102641
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Gastric Acid Suppressants on the Survival of Patients with Non-Small-Cell Lung Cancer Treated with Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitors: A Meta-Analysis

Abstract: Background. The influence of concomitant use of gastric acid suppressants (AS) on survival of patients with non-small-cell lung cancer (NSCLC) treated with epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) is inconsistent according to previous studies. We performed a meta-analysis to evaluate the effect of additional AS in patients with NSCLC taking TKIs. Methods. Relevant observational studies were identified by a search of Medline, Embase, and Web of Science databases. Only studies wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…An important outstanding question is whether PPI co-medication leads to more treatment failures with clinical impact among dasatinib users as the plasma exposure reduces more than 40%-60% with crystalline-based products. 4,12,13 Co-medication of PPIs and TKIs with pH-dependent absorption has previously been shown to be associated with reduced survival among lung cancer patients treated with erlotinib, 36,[49][50][51] gefitinib, [50][51][52] or dacomitinib. 51 More recent studies with dacomitinib or gefitinib have failed to replicate an association between concomitant PPI use and overall survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important outstanding question is whether PPI co-medication leads to more treatment failures with clinical impact among dasatinib users as the plasma exposure reduces more than 40%-60% with crystalline-based products. 4,12,13 Co-medication of PPIs and TKIs with pH-dependent absorption has previously been shown to be associated with reduced survival among lung cancer patients treated with erlotinib, 36,[49][50][51] gefitinib, [50][51][52] or dacomitinib. 51 More recent studies with dacomitinib or gefitinib have failed to replicate an association between concomitant PPI use and overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…4,12,13 Co-medication of PPIs and TKIs with pH-dependent absorption has previously been shown to be associated with reduced survival among lung cancer patients treated with erlotinib, 36,[49][50][51] gefitinib, [50][51][52] or dacomitinib. 51 More recent studies with dacomitinib or gefitinib have failed to replicate an association between concomitant PPI use and overall survival. 53,54 However, in the latter study, overall survival was decreased among "extensive users" of PPIs, defined as having at least one PPI prescription before and one prescription after cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several systemic reviews and meta-analyses also demonstrated that antacids are significantly associated with increased mortality 1578 risk in patients with lung cancer receiving EGFR-TKIs. [20][21][22] However, data of afatinib and PPIs remained limited. Second-generation EGFR-TKIs, such as afatinib and dacomitinib, showed a better survival benefit than first-generation EGFR-TKIs, such as gefitinib and erlotinib.…”
Section: Discussionmentioning
confidence: 99%
“…6 Previous retrospective or cohort studies reported the negative impact of PPIs on first-generation EGFR-TKIs, [7][8][9][10][11][12][13][14][15][16][17][18][19] and several systemic review and meta-analysis report similar results. [20][21][22] However, clinical data to evaluate the negative impact of PPIs on second-generation TKIs, such as afatinib or dacomitinib, are limited. Therefore, this retrospective cohort study was designed using Chang Gung Research Database (CGRD) to evaluate the impact of PPIs on first-line afatinib treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%